Ideologie, Geschichte und Verfassunggebung Legitimationsprobleme des ungarischen Grundgesetzes von 2012 - Varszegi, Mark (Beiträge zum ausländischen öffentlichen Recht und Völkerrecht, 2023)
Hungary's 2012 Basic Law, the most symbolic legal document of the Orbán era, has been in the crossfire of criticism throughout Europe from the moment it has been adopted. The objections refer to the exclusionary procedure of constitution-making, the ideological bias, and the undermining of the separation of powers. This study seeks well-founded legal dogmatic answers to these criticisms, using the achievements of the European and Hungarian constitutional traditions as a yardstick. Special attention is paid to the ups and downs of Hungarian legal history, to the period after 1989/90, and finally to the question of whether the Fundamental Law can be expected to have a long life in a democratic Europe.